(untitled) (Journal Of Educational and Psychological Researches, 2015)
The past few years have seen the development of the quantity and quality in the field of software, as it has become the word of electronic games of common terms used in the modern era. And the effects of this software it is working on a low ability to exercise social activities and the ability to perform the duties and turn away from physical exercise level and lead to the neglect of the child to develop friendships and social relations as a result of his over-zealous in use for a long time .olhz a stated research to achieve Ahavh which are: - Learn about social isolation among children Riyadh. - Identify statistically significant differences in social isolation, depending on the variable sex. - Identify statistically significant differences in social isolation, depending on the number of hours a child online gaming play. - Identify statistically significant differences in the number of hours a child’s play online gaming variable depending on the sex. The limited research on mothers governmental kids Riyadh who are in kindergarten in the city of Baghdad for the academic year (2014_2015) and achieve the objectives of research, the researcher build social isolation measure was the number of paragraphs of the scale "26" paragraph, as well as a researcher statistical analysis of the vertebrae by calculating the discriminatory power and show that paragraphs are all distinct and statistically significant with the exception of paragraphs (5_10), it is distinctive, as well as finding a relationship degree paragraph college degree .autam ensure the stability of the scale as a way retest reliability was "0.92" coefficient and this shows that good stability coefficient, increasing the application Alvakronbach equation and found that stability, "0.89" coefficient and this indicates that D. morally. The dish on a scale sample numbered "100" of mothers and children Riyadh research found the following results: The children of Riyadh have no social isolation, and there is no statistically significant difference in social isolation variable depending on the variable sex, as well as the presence of a statistically significant difference in social isolation variable among children Riyadh depending on the number of hours a child’s play online gaming, and finally the presence of a statistically significant difference in the number of hours of play Child online gaming and in favor of males. Then the researcher made a series of recommendations and proposals in the light of the search results.